2023
DOI: 10.17159/2078-516x/2023/v35i1a15068
|View full text |Cite
|
Sign up to set email alerts
|

Factors promoting and hindering sporting success among South African former Olympians from historically disadvantaged areas

Abstract: There are various contributing factors to sporting success among elite athletes, including Olympians. The purpose of this paper was to investigate the enablers and/or barriers to sporting success among South African former Olympians from historically disadvantaged areas (HDAs) using the SPLISS framework. This would enable an understanding of the factors that lead to sporting success among athletes from HDAs. A qualitative research design was employed for this study, whereby semi-structured interviews were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This finding is consistent with that of Mthombeni et al 17 who found that most former Olympians from HDA reported a lack of financial support, especially at the development level, being among the major hindrances of sporting success in South Africa. The lack of financial support may stem from the poor budget allocation to sports by government annually.…”
Section: Hindrancessupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with that of Mthombeni et al 17 who found that most former Olympians from HDA reported a lack of financial support, especially at the development level, being among the major hindrances of sporting success in South Africa. The lack of financial support may stem from the poor budget allocation to sports by government annually.…”
Section: Hindrancessupporting
confidence: 92%
“…University Sport South Africa (USSA), professional sports clubs, and academies are some of the structures that create a pathway for elite athletes to attain high-performance level. 17 Figure 1 shows a typical distribution mechanism for high-performance sport in South Africa. However, the school sport system which plays an important role for grass-roots sports development and a feeder system for elite sport in South Africa remains weak and dysfunctional as a very limited number of schools in HDA offer formalised sport programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The state of sports development in rural schools of South Africa is concerning, primarily because of the inadequate resources allocated for promoting PAs and sports (Mthombeni et al 2023 ). Consequently, there has been a substantial increase in non-communicable diseases (NCDs) like diabetes, hypertension, obesity, cardiovascular diseases, and cancer (WHO 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of adequate sports infrastructure in numerous rural schools continues to pose a challenge, mainly because of the enduring consequences of apartheid (Mthombeni et al 2023 ). Left unaddressed, this dearth of resources may result in the departure of extraordinarily gifted athletes and ultimately affect the competitiveness and overall calibre of the national sports teams (Kruger & Pienaar 2011 ).…”
Section: Introductionmentioning
confidence: 99%